2017
DOI: 10.1371/journal.pone.0173811
|View full text |Cite
|
Sign up to set email alerts
|

Environmental reservoirs of pathogenic mycobacteria across the Ethiopian biogeographical landscape

Abstract: The Mycobacterium genus comprises over one-hundred-and-fifty recognised species, the majority of which reside in the environment and many of which can be pathogenic to mammals. Some species of environmental mycobacteria may interfere with BCG vaccination efficacy and in tuberculin test interpretation. Examining biogeographic trends in the distribution of members of the mycobacteria across a number of physicochemical and spatial gradients in soil and water environments across Ethiopia using oligotyping identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 40 publications
(32 reference statements)
0
27
0
Order By: Relevance
“…Another study showed that higher elevation correlated to increased NTM up to 4000 m, with water temperatures between 17-23°C (i.e. similar to Hawaiian waters), and that environmental correlations and NTM species diversity may vary locally (King et al, 2017). Although patients can be cured, they are often re-infected with the same or another NTM species (Lipner et al, 2017).…”
Section: Background On Ntmmentioning
confidence: 99%
“…Another study showed that higher elevation correlated to increased NTM up to 4000 m, with water temperatures between 17-23°C (i.e. similar to Hawaiian waters), and that environmental correlations and NTM species diversity may vary locally (King et al, 2017). Although patients can be cured, they are often re-infected with the same or another NTM species (Lipner et al, 2017).…”
Section: Background On Ntmmentioning
confidence: 99%
“…The literature regarding microbial biogeography and community ecology has hitherto focused primarily on characterizing microbial populations on a "macro" scale-for instance, within non-spatially resolved environments such as soil and water [6][7][8]. Yet studies defining microbial consortia at various anatomical geographies now highlight the notion that microorganisms also display clear distribution patterns on this anatomical level, from site to site and tissue to tissue, varying in states of health and disease [9].…”
Section: Introductionmentioning
confidence: 99%
“…YCOBACTERIUM is a genus of Actinobacteria [1], which includes pathogens known to cause serious diseases in humans, such as Mycobacterium tuberculosis (Mtb) that causes global tuberculosis epidemic and accounts for more than 15 millions of deaths since 2000 [2]. Early and accurate detection of Mtb infection is an urgent need.…”
Section: Introductionmentioning
confidence: 99%